ChemInform Abstract: FeCl3 Mediated One‐Pot Route to Nitriles. Issue 1 (7th January 2014) - Ghosh, Pranab; Subba, Raju
Abstract A new simple method allows the conversion of aromatic aldehydes into nitriles in the presence of FeCl3 as promotor.